2019
DOI: 10.1038/s41467-019-09775-w
|View full text |Cite
|
Sign up to set email alerts
|

Association analyses identify 31 new risk loci for colorectal cancer susceptibility

Abstract: Colorectal cancer (CRC) is a leading cause of cancer-related death worldwide, and has a strong heritable basis. We report a genome-wide association analysis of 34,627 CRC cases and 71,379 controls of European ancestry that identifies SNPs at 31 new CRC risk loci. We also identify eight independent risk SNPs at the new and previously reported European CRC loci, and a further nine CRC SNPs at loci previously only identified in Asian populations. We use in situ promoter capture Hi-C (CHi-C), gene expression, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
210
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 189 publications
(220 citation statements)
references
References 71 publications
0
210
0
Order By: Relevance
“…None of the nominally significant genetic variants have known detrimental clinically relevant effects on gene function (Supporting Information Table S6). Rs3087967, which is located 3'UTP of C11orf53, is known to be associated with higher COLCA2 and C11orf53 expression in colon transverse tissue for C allele . However, little is known about COLCA2 and C11orf53 functions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the nominally significant genetic variants have known detrimental clinically relevant effects on gene function (Supporting Information Table S6). Rs3087967, which is located 3'UTP of C11orf53, is known to be associated with higher COLCA2 and C11orf53 expression in colon transverse tissue for C allele . However, little is known about COLCA2 and C11orf53 functions.…”
Section: Resultsmentioning
confidence: 99%
“…Genotyping was conducted using the Illumina HumanHap300, HumanHap240S and OmniExpressExome BeadChip 8v1 arrays. Standard quality control measures were applied as described previously . Untyped variants were imputed using SHAPEIT v2 and IMPUTEv2 softwares based on a merged reference panel comprising of 1,000 Genomes Project (phase 1, December 2013 release) and UK10K (April 2014 release) samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of high‐throughput technology, emerging evidence demonstrated that genetic alterations, including single‐nucleotide polymorphisms (SNPs), insertions, deletions, and copy number variations, were associated with the risk of various diseases including BC . Notably, SNPs, especially in irregular regions of protein‐coding and related with diseases, have been extensively studied and reported widely .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high-throughput technology, emerging evidence demonstrated that genetic alterations, including single-nucleotide polymorphisms (SNPs), insertions, deletions, and copy number variations, were associated with the risk of various diseases including BC. 5,6 Notably, SNPs, especially in irregular regions of protein-coding and related with diseases, have been extensively studied and reported widely. 7 The expression of the same lncRNA transcripts varies by different health conditions, age, tissues, even cells, which can indicate their potential as possible biomarkers and be predictive of diagnosis and prognosis of diseases.…”
Section: Introductionmentioning
confidence: 99%